Effects of functional maxillary orthopedics on the dimensions of the dental arches in patients with deep bite in primary dentition - Cardozo, María-Alejandra; Martínez, José-Manuel; Molina, Natalia; Hernández, Jesús-Alberto (Revista Estomatología, 2016)
Introduction: The skull cervico mandibular system needs of genetic, environmental and functional factors for development. The absence of funcionals stimuli generate change in growth and malocclusions. Objective: To evaluate the changes in the dimensions of the archs in patients with primary dentition and deep bite between 3 and 5 years, as a result of early treatment with functional orthopedic. Materials and Methods: Sample 20 children, between 3 and 5 years old, with complete primary dentition, deep bite, narrow arches, molar ratio straight terminal plane or distal step, who attended the Universidad del Valle. It was measured in plaster casts: Length, width intercanine, intermolar width, perimeter, overbite and overjet. Subsequently all patients were placed Planas direct Tracks elaborate indirectly, He underwent selective grinding and chewing orientation. After 6 months of treatment the second measurements were made. Results: The average initial overbite of the participants was 87.95%. It was found that the final overbite of patients was in average 25%. Differences between the two measurement times for all variables was found, although the upper perimeter were not statistically significant. The upper length and width intermolar had the highest percentage of change. Conclusions: Direct Planas tracks contributing to significant changes in the dimensions of the dental arches, when it implemented as early treatment for deep bite and/or distoclusion in the primary dentition.